Efeito do processo fermentativo na cinética e qualidade de hidromel - Matsuo, Nilson Yugo (2018)
Mead, a millenarian but forgotten beverage, presents a good alternative to add value to the raw material used, honey. Two mead samples will be prepared from a single 25 degree °Brix wort, added with pollen grains, which will be divided into two parts, one for conventional fermentation and the other for fermentation with immobilized yeast. The fermentation will occur at roughly 11,2 °C, after fermenting they will be matured for 142 days at 5,5 °C. At the end of this process, the beverages were submitted to physical-chemical and sensorial analysis, where we could observe differences between the traditional and immobilized yeast meads on their alcoholic volume (9.6% and 8.7% %), turbidity (34 and 26 NTU), and brightness, respectively.